Calculation of Capillary Rise Height of Soils by SWCC Model - Yuhan Li; Chen Zhang; Chenghao Chen; Hao Chen (Advances in Civil Engineering)
The maximum capillary rise height of soil is a complex system which is mainly determined by the distribution characteristics of soil pores. The tests of the rising height of capillary water on 8 kinds of soils by the method of vertical tube are widely conducted to measure the maximum capillary rise height. Based on the BCC model and principles of thermodynamics, the soil-water characteristic curve test is designed for the purpose of calculating the pore distribution of soil samples. A new method for calculating the maximum capillary rise height of soil is proposed by the author by using the distribution function of the soil pore. The coefficient β which reflects the relationship between the maximum capillary rise and the average pore radius of soils is utilized during the calculation process, and then the reference range of β for different soils is obtained according to series of experiments corresponding. The proposed calculation method offers an effective way to calculate the maximum capillary rise height, which can be applied to analyze the capillary effect area of relevant engineering problems.